Homogeneous immunoassay for cyclopiazonic acid based upon mimotopes and upconversion-resonance energy transfer - Pradanas-González Fernando; Peltomaa Riikka; Lahtinen Satu; Luque-Uría Álvaro; Más Vicente; Barderas Rodrigo; Maragos Chris M.; Canales Ángeles; Soukka Tero; Benito-Peña Elena; Moreno-Bondi María C. (Elsevier Ltd, 2025)
Strains of Penicillium spp. are used for fungi-ripened cheeses and Aspergillus spp. routinely contaminate maize and other crops. Some of these strains can produce toxic secondary metabolites (mycotoxins), including the neurotoxin α-cyclopiazonic acid (CPA). In this work, we developed a homogeneous upconversion-resonance energy transfer (UC-RET) immunoassay for the detection of CPA using a novel epitope mimicking peptide, or mimotope, selected by phage display. CPA-specific antibody was used to isolate mimotopes from a cyclic 7-mer peptide library in consecutive selection rounds. Enrichment of antibody binding phages was achieved, and the analysis of individual phage clones revealed four different mimotope peptide sequences. The mimotope sequence, ACNWWDLTLC, performed best in phage-based immunoassays, surface plasmon resonance binding analyses, and UC-RET-based immunoassays. To develop a homogeneous assay, upconversion nanoparticles (UCNP, type NaYF4:Yb3+, Er3+) were used as energy donors and coated with streptavidin to anchor the synthetic biotinylated mimotope. Alexa Fluor 555, used as an energy acceptor, was conjugated to the anti-CPA antibody fragment. The homogeneous single-step immunoassay could detect CPA in just 5 min and enabled a limit of detection (LOD) of 30 pg mL−1 (1.5 μg kg−1) and an IC50 value of 0.36 ng mL−1. No significant cross-reactivity was observed with other co-produced mycotoxins. Finally, we applied the novel method for the detection of CPA in spiked maize samples using high-performance liquid chromatography coupled to a diode array detector (HPLC-DAD) as a reference method.